Etat Des Lieux Et Gestion Des Semences Des Principales Céréales Cultivées Au Nord De La Côte d’Ivoire - Koffi, Kouablan Edmond; Yao, Saraka Didier Martial; Diarrassouba, Nafan; Siene, Laopé Ambroise Casimir (European Scientific Journal, ESJ, 2017)
The survey aims at assessing current managing status of organizations involves in the conservation of local genetic diversity of rice, maize, sorghum and pearl millet in seedbanks located in northern Côte d’Ivoire. An investigation was conducted with 100 respondents in charge of cereal seedbanks managing from Ferkessedougou and Ouangolodougou areas. The results at regional scale revealed two co-existing informal and formal systems for seedbanks management in these areas. The farmers’ seedbanks system or informal system was the main source of cereal seed supply for farmers and more important than the national or formal seedbank system. Only, farmers’ seedbanks of two crops, rice and maize were found in visited localities. The management of these farmers’ seedbanks was enabled by associations or cooperatives gathering more men (78.27%) than women (21.73%). Ninety percent (90%) of respondents were identified as saving 1 to 3 traditional varieties of cereal in these seedbanks managed by farmers in the studied region. The reveled difficulties in the farmers’ seedbanks management appeared mainly as informally organized seed system that must be a complementary approach to formal system or national seed system for genetic diversity preservation of local cereal varieties and also as a distribution channel of improved cereal varieties.